Study of the methods and their academic impact used in the teaching of spelling in the third cycle of Primary Education - Montaner Bueno, Andrés; Cánovas Herrero, María (Didáctica. Lengua y Literatura, 2025)
Spelling has always occupied a relevant place in school due to its value as a communicative component. However, over the years its teaching has been characterized by the use of traditional strategies and methods that have proven ineffective for learning of spelling. This study analyzes the orthographic knowledge that students in the sixth year of Primary Education have about the spellings b and v, the methods and techniques applied by the teachers of the subject Spanish Language and Literature to use spelling, and the treatment that the textbooks propose for teaching such spellings. The sample of participants was made up of 6 teachers and 117 students from three schools in the Region of Murcia. To determine the spelling knowledge of the students, five activities were specifically designed for this purpose. To determine the methodology used by teachers to teach spelling, a semi-structured interview technique was used. On the other hand, the treatment proposed on the teaching of spelling of b and v by three different publishers (Santillana, Anaya and SM publishing houses) was reviewed. The results obtained demonstrate that teachers use an appropriate methodology, since the results obtained by the students are quite positive and that the methodology proposed in the textbooks is the traditional one, since the exercises predominantly focus on repetition and the mechanization of writing.